Martingale approach to EWMA control charts for changes in exponential distribution - Yupaporn Areepong,; Novikov , Alexander (Penerbit ukm, 2008)

(untitled)
Exponentially weighted moving average (EWMA) procedure is a popular chart used for detecting small shifts of parameters of distributions in quality control and surveillance problems. The objective of this paper is to derive characteristics of a particular process such as Average Run Length (ARL) and Average Delay time (AD) under EWMA procedure assuming that observations follow an exponential distribution. Using the martingale approach we find explicit expressions for characteristics of EWMA as Average Run Length (ARL) and Average Delay time (AD). We compare the performance of the proposed expressions under EWMA and other procedures such as CUSUM based ARL and AD using some simulation studies